Editorial: Technologization of Global Citizenship Education as Response to Challenges of Globalization - Anatoli Rapoport (Research in Social Sciences and Technology, 2020)
Cultural, linguistic, and economic exchanges between communities, including nations, are as old as civilization itself, but only recently did such exchanges receive an appropriate and universally recognized name: globalization. Naming the process caused a significant shift in how globalization came to be perceived, and it has become an important issue in political agendas, economic policies, and cultural aspirations. In other words, globalization helped shape and refine debates about global interconnections and interdependence, universality of human rights, and the importance of economic and social justice.